What governs successful performance of a complex whole body movement: The Kovacs release-regrasp on horizontal bar? - Hiley, M. J.; Yeadon, M. R. (Journal of Biomechanics, 2016)
The Kovacs is a release and regrasp skill performed on the horizontal bar in men?s artistic gymnastics. It is a popular skill in elite competitive gymnastics with over 40% of male gymnasts performing a variation of the Kovacs at the London 2012 Olympics. In the qualifying competition 84% of Kovacs were successfully regrasped, with the remaining 16% resulting in a fall. The aim of the present study was to determine why some gymnasts are more successful than others at regrasping the bar, with a secondary aim to determine how a less successful gymnast could alter his technique in order to become more successful. Nine performances of the Kovacs by each of two gymnasts, one 100% successful and one 11% successful, were analysed to determine differences in release and regrasp parameters. The technique of the less successful gymnast was optimised using a computer simulation model to increase the percentage of catches (success rate). The successful gymnast had larger and more consistent release windows and a radial velocity towards the bar at regrasp. The less successful gymnast had higher horizontal velocity at release and a mean radial velocity away from the bar at regrasp. Optimising his simulated technique increased the rate of success from 11% to 93%. The actions prior to release were performed earlier than in the recorded performances leading to a more vertical path of the mass centre at release and a radial velocity towards the bar at regrasp.